Computed tomography coronary angiography for patients with heart failure (CTA-HF): a randomized controlled trial (IMAGE-HF 1C). (26th June 2020) - Chow, Benjamin J.W.; Coyle, Doug; Hossain, Alomgir; Laine, Mika; Hanninen, Helena; Ukkonen, Heikki; Rajda, Miroslav; Larose, Eric; Hartikainen, Juha; Mielniczuk, Lisa; Kass, Malek; Connelly, Kim A.; et al.
Abstract: Aims: This randomized controlled trial sought to determine the financial impact of an initial diagnostic strategy of coronary computed tomography angiography (CCTA) in patients with heart failure (HF) of unknown aetiology. Invasive coronary angiography (ICA) is used to investigate HF patients. CCTA may be a non-invasive cost-effective alternative to ICA. This randomized controlled trial sought to determine the financial impact of an initial diagnostic strategy of coronary computed tomography angiography (CCTA) in patients with heart failure (HF) of unknown aetiology. Methods and results: This multicentre, international trial enrolled patients with HF of unknown aetiology. The primary outcome was the cost of CCTA vs. ICA strategies at 12 months. Clinical outcomes were also collected. An 'intention-to-diagnose' analysis was performed and a secondary 'as-tested' analysis was based on the modality received. Two hundred and forty-six patients were randomized (age = 57.8 ± 11.0 years, ejection fraction = 30.1 ± 10.1%). The severity of coronary artery disease was similar in both groups. In the 121 CCTA patients, 93 avoided ICA. Rates of downstream ischaemia and viability testing were similar for both arms. There were no significant differences in the composite clinical outcomes or quality of life measures. The cost of CCTA trended lower than ICA [CDN −871 (confidence interval, CI −4116 to 3028)]. Using an 'as-tested' analysis, CCTA was associated with a decrease in healthcare costs (CDN −2932, 95% CI −6248 to 746). Conclusion: In patients with HF of unknown aetiology, costs were not statistically different between the CCTA and ICA strategies. Clinical Trials.gov: NCT01283659